Nanocomposite structures and dispersions - Capek, Ignac (Elsevier, 2019)
Nanocomposite Structures and Dispersions deals with the preparation of gelled, branched and crosslinked nanostructured polymers in the solution free radical polymerization and controlled/living radical polymerization and polymer and composite nanoparticles and nanostructures in disperse systems, the kinetics of direct and inverse disperse polymerizations (microemulsion, miniemulsion, emulsion, dispersion and suspension polymerization), the bottom-up approach building of functionalized nanoparticles, modelling of radical microemulsion polymerization, the characterization of traditional and non-traditional polymer dispersions, the collective properties of nanomaterials and their (bio)applications. This book is designed to bridge that gap and offers several unique features. First, it is written as an introduction to and survey of nanomaterials with a careful balance between basics and advanced topics. Thus, it is suitable for both beginners and experts, including graduate and upper-level undergraduate students. Second, it strives to balance the colloidal aspects of nanomaterials with physical principles. Third, the book highlights nanomaterial based architectures including composite or hybrid conjugates rather than only isolated nanoparticles. A number of ligands have been utilized to biodecorate the polymer and composite nanocarriers. Finally, the book provides an in depth discussion of important examples of reaction mechanisms of bottom-up building of functionalized nanoparticles, or potential applications of nanoarchitectures, ranging from physical to chemical and biological systems.